PENGARUH MODEL PROBLEM BASED LEARNING (PBL) TERHADAP AKTIVITAS DAN HASIL BELAJAR SISWA - Mei Rukmana; Tri Jalmo; Berti Yolida (Universitas Lampung, 2013)
Students achievement is the ultimate goal is linked to the implementation of the learning process. Observations in X grade Senior High School 1 Natar, known that student activity and achievement is low. This study aimed to determine the effect of PBL models in improving student activity and achievement. The design was non-equivalent control group. The sample was class X3and X5 selected by purpossive sampling. This data is quantitative and qualitative form. Quantitative data obtained average value of the pretest, posttest and N-gain on Biodiversity material. Qualitative data obtained percentage average of students activities and responses of uses PBL models was analyzed descriptively. The results showed that the use of PBL models can improve student learning activities with an average of 66% it is also evident from the increase observed for all aspects. Students achievement in the experimental class also increase with average value of N-gain is 67,38. In addition, all students gave positive response to the use of PBL models. Thus, it can be concluded that the uses PBL models is influential in increasing the students activity and achievement. Keywords: biodiversity, PBL models, students learning activities and achievement.